PERSON DEIXIS IN USA PRESIDENTIAL CAMPAIGN SPEECHES - Nanda Anggarani Putri; Eri Kurniawan (University of Kuningan, 2015)
Abstract: This study investigates the use of person deixis in presidential campaign speeches. This study is important because the use of person deixis in political speeches has been proved by many studies to give significant effects to the audience. The study largely employs a descriptive qualitative method. However, it also employs a simple quantitative method in calculating the number of personal pronouns used in the speeches and their percentages. The data for the study were collected from the transcriptions of six presidential campaign speeches of Barack Obama and Mitt Romney during the campaign rally in various places across the United States of America in July, September, and November 2012. The results of this study show that the presidential candidates make the best use of pronouns as a way to promote themselves and to attack their opponents. The results also suggest that the use of pronouns in the speeches enables the candidates to construct positive identity and reality, which are favorable to them and make them appear more eligible for the position.Keywords: person deixis, presidential campaign speeches, Barack Obama, Mitt RomneyÂ Â